Konstruksi Kewenangan Pemerintah Kabupaten/Kota di Aceh dalam Penanganan Urgensi Pandemi Covid 19 - T. Surya Reza (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
The legal issue of the regulation norms and policies of the Government of the District/City of Aceh in dealing with the COVID-19 pandemic is the imposition of sanctions by the policy maker without the presence of a court ruling granting detention that officials have performed judicial duties in general. This policy makes the sanctions very subjective. The main issue in this article is how to construct the authority of the district or city government in Aceh in the emergency treatment of the COVID-19 pandemic. The type of research method used is normative jurisprudence, with a conceptual approach from primary or secondary and analyzed deskripsitf. Based on the known results, the regulation in the administration has violated a very fundamental legal principle, as it is known that the provisions of the sanctions in the Regulation/Regulation with provisions in the Law No. 12 Year 2011 on the Creation of Regulations Legislative, regulations containing sanctions only the Law or Perpu and Perda/Qanun. Sanctions are a reduction in the rights of a person or a citizen, and because they are a decrease in rights, the product must be produced by the government and the representatives of the public (the Council of People's Representation of the District or City/DPRK). The administrator has no authority to impose administrative sanctions in juncto with other laws because it is not in accordance with imperative and facultative.